Allergic Bronchopulmonary Aspergillosis–A Luminal Hypereosinophilic Disease With Extracellular Trap Cell Death - Ueki, Shigeharu; Hebisawa, Akira; Kitani, Masashi; Asano, Koichiro; Neves, Josiane S. (Frontiers in Immunology, 2018)
Allergic bronchopulmonary aspergillosis (ABPA) is characterized by an early allergic response and late-phase lung injury in response to repeated exposure to Aspergillus antigens, as a consequence of persistent fungal colonization of the airways. Here, we summarize the clinical and pathological features of ABPA, focusing on thick mucus plugging, a key observation in ABPA. Recent findings have indicated that luminal eosinophils undergo cytolytic extracellular trap cell death (ETosis) and release filamentous chromatin fibers (extracellular traps, ETs) by direct interaction with Aspergillus fumigatus. Production of ETs is considered to be an innate immune response against non-phagocytable pathogens using a “trap and kill” mechanism, although eosinophil ETs do not promote A. fumigatus damage or killing. Compared with neutrophils, eosinophil ETs are composed of stable and condensed chromatin fibers and thus might contribute to the higher viscosity of eosinophilic mucus. The major fate of massively accumulated eosinophils in the airways is ETosis, which potentially induces the release of toxic granule proteins and damage-associated molecular patterns, epithelial damage, and further decreases mucus clearance. This new perspective on ABPA as a luminal hypereosinophilic disease with ETosis/ETs could provide a better understanding of airway mucus plugging and contribute to future therapeutic strategies for this challenging disease.